Incidence of workplace violence against nurses among Chinese hospitals: A meta‐analysis. (17th August 2021) - Liu, Xin; Yang, Haojie; Hu, Yule; Zhou, Yanjun; Wang, Jiahong; Dong, Lili; Zhang, Min; Liang, Tao
Abstract: Aims: To explore the incidence of workplace violence against nurses in Chinese hospitals. Background: Previous systematic reviews on the incidence of workplace violence against Chinese health care workers did not include many articles published in Chinese. Although several studies have investigated cases of violence against health care providers in China, no meta‐analysis has been conducted to assess the incidence of violence against Chinese nurses. Evaluation: In this study, relevant data were retrieved from studies published up to July 2020. A meta‐analysis was conducted using R software (Version 4.0). Key findings: The 12‐month incidence of workplace violence among Chinese nurses was 71% (95% CI 67%–75%), and verbal violence was the most common sub‐type of violence (63%, 95% CI 58%–67%). Conclusion: Chinese nurses are at a high risk of violence at workplace. Hospital managers should explore ways to reduce violence against their employees, especially the younger nurses who work in secondary hospitals. Implications for Nursing Management: The findings of this study highlight the need to enhance the legal system in terms of laws meant to effectively mitigate violence against nurses in Chinese hospitals. Measures should be particularly taken to protect younger nurses who work in secondary hospitals.